A note on variable step-size formulation of a Simpson's-type second derivative block method for solving stiff systems. (February 2017) - Ramos, Higinio; Singh, Gurjinder
Abstract: In this paper, a variable step-size formulation of a Simpson's-type second derivative block method is considered as an embedded-type method. This embedded-type method is more effective than its existing fixed step-size counterpart. The numerical experiments considered revealed the superiority of the variable step-size version of the method in comparison with methods of similar characteristics in the literature.